LISA: Heliocentric formation design for the laser interferometer space antenna mission. Issue 11 (1st June 2021) - Joffre, Eric; Wealthy, Dave; Fernandez, Ignacio; Trenkel, Christian; Voigt, Philipp; Ziegler, Tobias; Martens, Waldemar
Abstract: The LISA (Laser Interferometer Space Antenna) mission has been selected by the European Space Agency's Science Programme Committee as the third large-class mission of the Cosmic Vision Programme, addressing the science theme of the Gravitational Universe. With a planned launch date in 2034, LISA will be the first ever space-borne Gravitational Wave observatory, relying on laser interferometry between three spacecraft orbiting the Sun in a triangular formation. Airbus is currently leading an industrial Phase A system study on behalf of the European Space Agency. The paper will address the astrodynamics challenges associated with the LISA constellation design, driven by tight requirements on the geometric quality metrics of the near equilateral formation.